Social media and virtual sisterhood: The Instagram account @perempuanberkisah as a space for women's solidarity - Andina, Tri Kurnia Revul; Pembayun, Estavita Chantik; Fahadi, Prasakti Ramadhana (Universitas Negeri Yogyakarta, 2023)
The practical and interactive nature of social media has played a pivotal role in fostering unity among women. Social media has evolved into platforms for women to express their worries, share their fears, discuss their problems, and be more emphatetic towards each other. In this virtual realm, a distinct form of solidarity has emerged, allowing women to amplify their voices beyond the confines of the non-virtual world. An exemplary illustration of this phenomenon is the Instagram account @perempuanberkisah, which actively advocates for women's issues, particularly focusing on cases of violence. @perempuanberkisah curates diverse content, frequently featuring themes related to violence, including posts tagged #kisah18+ and #triggerwarning. Notably, the content goes beyond mere storytelling; it includes ongoing support for the individuals sharing their experiences, both from the @perempuanberkisah team and the broader community of women, as evidenced by the supportive comments flooding the posts. This study aims to delve into the virtual solidarity that has taken root among women within the @perempuanberkisah community, particularly within the context of contents labelled #kisah18+ and #triggerwarning. This research uses the virtual etnography method with descriptive-critical analysis. The result shows that virtual solidarity emerges from the empathy shown by @perempuanberkisah and women on Instagram through almost the entirety of their content. The sense of belonging and shared experience have generated solidarity among women despite the lack of interactions beyond the virtual space.